2019
DOI: 10.1002/cam4.2256
|View full text |Cite
|
Sign up to set email alerts
|

What are the clinical symptoms and physical signs for non‐small cell lung cancer before diagnosis is made? A nation‐wide multicenter 10‐year retrospective study in China

Abstract: Background Most lung cancer patients are diagnosed after the onset of symptoms. However, whether the symptoms of lung cancer were independently associated with the diagnosis of lung cancer is unknown, especially in the Chinese population. Methods We conducted a 10 years (2005‐2014) nationwide multicenter retrospective clinical epidemiology study of lung cancer patients diagnosed in China. As such, this study focused on nonsmall cell lung cancer (NSCLC). We calculated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 26 publications
3
30
1
Order By: Relevance
“…First, LADC was the dominant type in previous reports, followed by LUSC and SCLC. [ 16 ] However, the proportion of LUSC was higher than that of LADC in our study, indicating an alteration in histologic distribution within patients lacking a targetable oncogene driver. This discrepancy with previous reports could be due to the higher ratio of patients in LADC with targetable oncogene drivers.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…First, LADC was the dominant type in previous reports, followed by LUSC and SCLC. [ 16 ] However, the proportion of LUSC was higher than that of LADC in our study, indicating an alteration in histologic distribution within patients lacking a targetable oncogene driver. This discrepancy with previous reports could be due to the higher ratio of patients in LADC with targetable oncogene drivers.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, 88.7% (165/186) of the patients were male, which was higher than that of some reports in China. [ 16 ] This may be due to the exclusion of EGFR or ALK ‐related driver gene mutations, as a considerable proportion of patients with TKI‐related driver gene mutations were nonsmoking patients. Therefore, the therapeutic response and long‐term prognosis of LUSC and male patients with no EGFR or ALK ‐related driver gene mutations are worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of haemoptysis, cough and chest pain was much higher across all stages than in our sample; however, dyspnoea was less frequent in the Chinese study. 6 With regard to the number of symptoms at diagnosis, a study published by Walter et al showed that 19% of lung cancer patients had two or more symptoms and 8.8% had three or more symptoms at diagnosis, 12 figures very similar to ours (21% and 12%, respectively). Unfortunately, this study did not break down the number of symptoms by tumour stage at diagnosis.…”
Section: Discussionsupporting
confidence: 81%
“…Lung cancer is the most common form of cancer and the leading cause of cancerrelated mortality worldwide, resulting in about 1.7 million deaths each year. 1 Nonsmall-cell lung cancer (NSCLC) accounts for approximately 85-90% of all lung cancer cases, 2 inherently having a noticeable impact on health-care budgets. Among those cases, 10-20% of white patients and about 48% of Asian patients carry mutations in the epidermal growth factor receptor (EGFR) that play a key role in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%